Public Opinion on Change in Reservation Policy - N, Vishal (International Journal of Psychosocial Rehabilitation, 2020)
This research paper describes the history and present status of reservation system in India. Reservation in education has proved to be an active tool of social transformation by providing opportunities to backward and marginalized section of society in the public employment, education and legislatures but needs major reformations as society has moved forward and is legally equipped to ensure social development. The objective of the study is to analyse the difference between need of reservation policy and gender of the respondents.For the purpose of this research, descriptive method was followed and the data was collected through personal survey analysis. The SPSS software by IBM was used to calculate the descriptive statistics. The sample size was 1640. Dependent variablesare Need for change in reservation policy, Usage of reservation policy, Economically weaker section, Creamy layer among SC/ST, Reconsidering FC’s policies. Independent variables areAge, gender, monthly income. Various tools like ANOVA, Chi Square, and sample t test were used. The analysis found that there is a significant association between the usage of reservation policy and age of the respondent. The conclusion obtained through this research work is that reservation policy is a double edged knives, ie. it helps one and deprives another.